2014
DOI: 10.7314/apjcp.2014.15.5.1905
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiations Induce Apoptosis in TRAIL Resistant Cancer Cells: in vivo and in vitro Analysis

Abstract: Increasingly it is being realized that despite considerable advancements in therapeutic interventions related to treatment of cancer, satisfactory results are still difficult to achieve. Rapidly accumulating evidence has started to shed light on the fact that cancer cells escape from death via constitutive activation of pro-survival signaling cascades. Cell biology and genetics have extensively enhanced our current understanding of the molecular mechanisms that underlie loss of apoptosis in cancer cells. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…These results suggested that PDGFR-β-targeted therapy combined with RT was able to reduce the expression of cyclin B1, thereby blocking cells in the G2/M period and increasing the radiosensitivity of the cells. Apoptosis is regulated by the programmed cell death gene and is the main form of tumor cell death induced by radiation therapy (24). The present study demonstrated that the apoptosis index of the KD+RT group was higher than the other three groups, and that this group had the most TUNEL-positive cells.…”
Section: A B C Dmentioning
confidence: 45%
“…These results suggested that PDGFR-β-targeted therapy combined with RT was able to reduce the expression of cyclin B1, thereby blocking cells in the G2/M period and increasing the radiosensitivity of the cells. Apoptosis is regulated by the programmed cell death gene and is the main form of tumor cell death induced by radiation therapy (24). The present study demonstrated that the apoptosis index of the KD+RT group was higher than the other three groups, and that this group had the most TUNEL-positive cells.…”
Section: A B C Dmentioning
confidence: 45%
“…Tolerance to radiation has become one of the most challenging problems in cancer therapy. Cells undergo a complicated pathophysiological process after receiving radiation, involving abnormal activation of multiple signaling pathways (Jung et al, 2010;Xu et al, 2011), DNA damage of genes, the abnormal expression of proteins with the capacity of promoting DNA repair (Kasid et al, 1987;Kitahara et al, 2002;Fukuda et al, 2004), angiogenesis (Magnon et al, 2007), autophagy (Chaachouay et al, 2011;Zhuang et al, 2011), and apoptosis (Silva et al, 2014). Although these findings help to raise awareness and understanding of the cell radiosensitivity, the mechanism of this process is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…There is a list of newly emerging scientific evidence highlighting molecular mechanisms to enhance or restore TRAIL induce apoptosis in cancer cells (Zhao et al, 2011;Huang et al, 2012;Jiang et al, 2013;Silva et al, 2014). Wide ranging phytochemicals are currently being tested for efficacy.…”
Section: Crosstalk Between Trail Induced Signaling Machinery and Automentioning
confidence: 99%